0012 Molecular Correlates of Operational Blast and Associated Sleep Disturbances. (12th April 2019) - Haghighi, Fatemeh; Ge, Yongchao; Wang, Zhaoyu; Mendelev, Natalia; Choi, InBae (Brian); Vitale, Amanda; Wilson, Caroline; Nemes, Jeffrey; LaValle, Christina; Kamimori, Gary; Shear, Deborah; Boutte, Angela; et al.
Abstract: Introduction: Injuries from exposure to explosive blasts rose dramatically during Operation Iraqi Freedom and Operation Enduring Freedom. Over 80% of the traumatic brain injuries incurred in Iraq and Afghanistan are classified as mild, with sleep disturbances being one of the most commonly reported comorbid chronic symptoms. We have undertaken human studies involving military and law enforcement personnel involved in operational breaching where they are typically in close proximity to repeated controlled, low-level blasts. Sleep disturbances are also in the top three reported symptoms by these participants of operational training, motivating investigations of blast-related neurotrauma and associated sleep disturbances. Methods: Although the data collected involves multiple operational breaching sites, here we present data from one site including 34 participants where blood samples are collected pre-post operational training. We performed genome-scale DNA methylation profiling using the Illumina Infinium HumanMethylation 450K BeadChip platform covering all coding genes and whole genome transcription profiling via RNA-seq. Results: We examined at baseline (pre operational breaching) whether the number of accumulative blast exposure events during a career in military service is associated with changes in transcriptional regulation. We defined low exposure as those with ≤39 reported blast exposures and the high group with ≥40 blast exposures. We found differences in transcriptional regulation (differential DNA methylation) in the PAX8-AS1 gene promoter region, which is an antisense transcript overlapping the paired box 8 (PAX8) gene. Recently, genome-wide association studies have implicated genetic variants associated with PAX8 and sleep duration. Conclusion: These data are compelling in establishing the framework for studies of operational blast samples for identification of chronic biomarkers of blast-related TBI in relation to sleep disturbances, which will allow us to gain further insight into the molecular mechanisms underlying blast-related TBI and associated chronic sleep disturbances. These are crucially relevant in studies of sleep disturbances and mild TBI in our Veteran population. Support (If Any): Research supported by CX001395 and RX001705.